A Management of Water Quality Parameters In Cultivating Vaname Shrimp (Litopenaeus vannamei) In Intensive Tambak PT. Aneka Tambak Oseana Nusantara , NTB - Pieter Amalo; Riris Yuli Valentine; Catur Pramono Adi; Restye Putri Geofani Mbura (Universitas Insan Cendekia Mandiri, 2023)
One of the causes of failure in vaname shrimp cultivation is poor management of water quality during the production period. Therefore, water quality management during the maintenance process is absolutely necessary. To study water quality management in growing white vaname shrimp (Litopenaeus vannamei) at PT. Aneka Pond Oceana Nusantara, NTB. Knowing the obstacles and solutions in managing water quality during practical activities at PT. Aneka Pond Oceana Nusantara, NTB. The technique for rearing vaname shrimp (Litopenaues vannamei) is as follows: preparing the container; the container is filled with water; fry selection; feeding interval; The results of water quality management strategies for vaname shrimp cultivation include: temperature (27 -28℃), morning brightness (30-118 cm), afternoon (28-108 cm). Morning pH (7.7- 8.2) afternoon (7.8-8.6), morning DO (5.87-6.18 ppm) evening (4.82-5.92 ppm), salinity (30- 33).